THE HIERARCHY OF COMPONENT FOR TASKS SOLUTION IN THE COURSE OF “LINEAR ALGEBRA” (Journal of Information Technologies in Education (ITE), 2009)
In the present article the case in point is an application of new informational technologies in the process of teaching Linear Algebra in Kherson State University. The component-oriented approach to the teaching Linear Algebra is examined as well as hierarchy of components which is used in the system and advantages of such approach in comparison with traditional approach.
Keywords: distance learning; educational software; linear algebra